MOBILITAS PENDUDUK DI PROPINSI BALI SEBELUM DAN SEMASA KRISIS MONETER BESERTA DAMPAKNYA - Ida Bagoes Mantra (Populasi, 1998)
The relatively low negative impact of the Indonesian economic crisis on the province of Bali is due to the ability of the agriculture and tourist industry in the province to sustain this impact. The price of non food crop production such as cloves, coffee, cocoa, and cashew nuts is very high, and this is partially as a result of the stable peace and security enjoyed by the province. The high trend of foreign and national tourist to Bali which had declined drastically because of the demonstrations and chaos in some cities on the Java Island, has no once again picked up momentum.The prevailing peace and stability in the Island of Bali is utilised by the Indonesian Chinese have taken asylum in this province as their houses and property in the other provinces were burnt and destroyed in the previous upheavals. The exodus of Chinese to Bali during that crisis led to a Bali during that crisis led to a negative impact on the population, economic, and cultural sector of the province.